Structural Reliability Analysis Using Group Teaching Optimization Algorithm. Issue 2 (April 2021) - Cheng, Jiaming; Jin, Hui
Abstract: Conventional First order reliability method (FORM) usually encounters divergence and non-convergence for high nonlinear performance functions. This paper puts forward an improved FORM coupling with a newly raised metaheuristic optimization algorithm, that is, Group teaching optimization algorithm (GTO). The GTO algorithm is inspired by grouping teaching strategy, featured by no additional control parameters, and has shown excellent global search ability for high nonlinear problems. Thus, the GTO algorithm is utilized to solve the equivalent constrained optimization problem according to the first order reliability theory. The implementation procedure of the proposed method is then presented in this paper. A numerical example is employed to verify the performance of the proposed method. Traditional reliability methods and PSO-based FORM are also introduced to compared with the proposed approach. The simulation results prove that the proposed method provides good performance in terms of computational efficiency and accuracy.